Corporate strategy, green knowledge, and sustainable performance: a study of Colombia’s triple bottom line (2025)
This study explores how Corporate Strategy and Green Knowledge influence the development of the Triple Bottom Line (economic, social, and environmental) in Colombian companies. Using a quantitative approach and Structural Equation Modeling, it tests three hypotheses about the relationships between these factors. The findings aim to guide companies in adopting sustainable practices that enhance competitiveness and profitability.